UPPER BOUNDS FOR RUIN PROBABILITY IN A CONTROLLED GENERAL RISK PROCESS WITH RATE OF INTEREST IS A FIRST - ORDER (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we study a controlled general risk process where claim is homogeneous Markovchain and rate of interest is a first-order autoregressive process. We assume that claim ishomogeneous Markov chain, take a countable number of nonnegative values and rate of interestis a sequence of non-negative random variables what it satifies a first-order autoregressiveprocess. Generalized Lundberg inequalities for ruin probability of this process are derived bythe Martingale approach.